PENGARUH KUALITAS PRODUK DAN CUSTOMER PERCEIVED VALUE TERHADAP KEPUASAN PELANGGAN PADA UMKM KERIPIK NANAS SEROJA KELOMPOK TANI TUGU MANDIRI KOTA DUMAI - Suprapto, Bambang; Amelia, Syifa; hasanah, Siti Nur (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study is to analyze the influence of product quality and customer-perceived value on customer satisfaction at Seroja Pineapple Chips MSMEs in Dumai City. The study used a quantitative approach with a survey method. A sample of 103 respondents was selected using a purposive sampling technique from a population of 446 students of STIE Tuah Negeri Dumai with a 10% error rate. Data was collected through questionnaires and analyzed using multiple linear regression with SPSS 24. The results showed that product quality and customer perceived value partially and simultaneously have positive and significant effect on customer satisfaction. This finding indicates that increasing product quality and consumer-perceived value can increase customer satisfaction with Seroja pineapple chips